Quantifying bunch-mode influence on photon-counting detectors at SPring-8 - Yasuhiko Imai; Takaki Hatsui (Journal of Synchrotron Radiation, 2024)
Count-loss characteristics of photon-counting 2D detectors are demonstrated for eight bunch-modes at SPring-8 through Monte Carlo simulations. As an indicator, the effective maximum count rate was introduced to signify the X-ray intensity that the detector can count with a linearity of 1% or better after applying a count-loss correction in each bunch-mode. The effective maximum count rate is revealed to vary depending on the bunch-mode and the intrinsic dead time of the detectors, ranging from 0.012 to 0.916 Mcps (megacounts per second) for a 120 ns dead time, 0.009 to 0.807 Mcps for a 0.5 µs dead time and 0.020 to 0.273 Mcps for a 3 µs intrinsic detector dead time. Even with equal-interval bunch-modes at SPring-8, the effective maximum count rate does not exceed 1 Mcps pixel−1. In other words, to obtain data with a linearity better than 1%, the maximum intensity of X-rays entering the detector should be reduced to 1 Mcps pixel−1 or less, and, in some cases, even lower, depending on the bunch-mode. When applying count-loss correction using optimized dead times tailored to each bunch-mode, the effective maximum count rate exceeds the values above. However, differences in the effective maximum count rate due to bunch-modes persist. Users of photon-counting 2D detectors are encouraged to familiarize themselves with the count-loss characteristics dependent on bunch-mode, and to conduct experiments accordingly. In addition, when designing the time structure of bunch-modes at synchrotron radiation facilities, it is essential to take into account the impact on experiments using photon-counting 2D detectors.